Inovasi Media Pop-Up Book Berbasis Potensi Lokal Terintegrasi Tri-N untuk Meningkatkan Berpikir Kritis Siswa Sekolah Dasar - Zulfiati, Heri Maria; Sudigdo, Anang; Whesli , Hendika (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2024)
This study aims to: (1) determine the needs of teachers and students to improve critical thinking; (2) develop a pop-up book media innovation design based on local potential integrated tri n to improve critical thinking; (3) test the feasibility of media pop up book based on local potential integrated tri n to improve critical thinking; (4) test the effectiveness of media pop up book based on local potential integrated tri n to improve critical thinking. The research method used is Research and Development (R&D) research using the Borg and Gall development model. The development model used at Borg & Gall is described in 10 implementation stages. Data collection was carried out through interviews, questionnaires, and tests. This research uses instruments that have been validated by experts. Data is presented quantitatively and qualitatively. The effectiveness of learning media was tested using the independent t-test and n-gain test.  Research subjects included a limited test of 10 students at Jaraksari 1 Elementary School an operational field test of 21 students at Jaraksari 3 Elementary School as the experimental class and 22 students at Jogoyitnan Elementary School as the control class. The research results show that: (1) analysis of student and teacher needs shows that pop-up book media based on integrated local potential is essential to improve the dimensions of critical thinking; (2) tri-n integrated local potential based pop-up book media developed through the Canva and Quizizz sites; (3) the validity of the Tri-N integrated local potential-based pop-up book media received a very decent title with an average of 93%; (4) the use of pop-up book media is effective in improving students' critical thinking with t-test results with sig (2-tailed) values, namely 0.000 < 0.05 and t count 5.011 > t table 1.681 as well as class n-gain scores experimental 0.577778 which is higher than the control class 0.285714.